Harrison's infectious diseases - Kasper, Dennis L. ;Fauci, Anthony S. (New York : McGraw Hill Education, 2010)
Featuring the chapters on infectious diseases that appear in Harrison's Principles of Internal Medicine, 17e, this expert clinical companion delivers the latest knowledge in the field, backed by the scientific rigor and reliability that have defined Harrison's. Inside you'll find coverage that reflects the expertise of renowned editors and contributors--presented in a stand-alone format that makes it ideal for the classroom, the wards, or exam/certification preparation. --Book Jacket
Machine generated contents note: SECTION I INTRODUCTION TO INFECTIOUS DISEASES 1.Introduction to Infectious Diseases: Host-Pathogen Interactions / Dennis L. Kasper 2.Molecular Mechanisms of Microbial Pathogenesis / Gerald B. Pier 3.Immunizaation Principles and Vaccine Use / Mark Miller 4.Health Advice for International Travel / Phyllis E. Kozarsky 5.Laboratory Diagnosis of Infectious Diseases / Andrew B. Onderdonk 6.Microbial Bioterrorism / Anthony S. Fauci SECTION II FEVER AND APPROACH TO THE FEBRILE PATIENT 7.Fever and Hyperthermia / Reuven Porat 8.Fever and Rase / Kenneth M. Kaye 9.Fever of Unkonwn Origin / Michael V. Callahan 10.Atlas of Rashes Associated with Fever / Elaine T. Kaye 11.Infections in Patients with Cancer / Robert Finberg 12.Infections in Transplant Recipients / Joyce Fingeroth 13.Health Care Associated Infections / Robert A. Weinstein 14.Approach to the Acutely Ill Infected Febrile Patient / Dennis L. Kasper Note continued: 15.Severe Sepsis and Septic Shock / Robert S. Munford SECTION III INFECTIONS IN ORGAN SYSTEMS 16.Pharyngitis, Sinusitis, Otitis, and Other Upper Respiratory Tract Infections / Merle A. Sande 17.Pneumonia / Richard Wunderink 18.Bronchiectasis and Lung Abscess / Steven E. Weinberger 19.Infective Endocarditis / Adolf W. Karchmer 20.Pericardial Disease / Eugene Braunwald 21.Infections of the Skin, Muscle, and Soft Tissues / Dennis L. Stevens 22.Osteomyelitis / Jeffrey Parsonnet 23.Infectious Arthritis / Lawrence C. Madoff 24.Intraabdominal Infections and Abscesses / Dennis L. Kasper 25.Acute Infectious Diarrheal Diseases and Bacterial Food Poisoning / Stephen B. Calderwood 26.Acute Appendicitis and Peritonitis / William Silen 27.Urinary Tract Infections, Pyelonephritis, and Prostatitis / Walter E. Stamm 28.Sexually Transmitted Infections: Overview and Clinical Approach / King K. Holmes Note continued: 29.Meningitis, Encephalitis, Brain Abscess, and Empyema / Kenneth L. Tyler 30.Chronic and Recurrent Meningitis / Morton N. Swartz 31.Chronic Fatigue Syndrome / Stephen E. Straus 32.Infectious Complications of Burns and Bites / Florencia Pereyra SECTION IV BACTERIAL INFECTIONS pt. 1 Approach to Therapy for Bacterial Diseases 33.Treatment and Prophylaxis of Bacterial Infections / Ronald E. Polk pt. 2 Diseases Caused by Gram-Positive Bacteria 34.Pneumococcal Infections / Daniel M. Musher 35.Staphylococcal Infections / Franklin D. Lowy 36.Streptococcal and Enterococcal Infections / Michael R. Wessels 37.Acute Rheumatic Fever / Jonathan R. Carapetis 38.Diphtheria and Other Infections Caused by Corynebacteria and Related Species / John R. Murphy 39.Infections Caused by Listeria Monocytogenes / Daniel A. Portnoy 40.Tetanus / Elias Abrutyn 41.Botulism / Elias Abrutyn Note continued: 42.Gas Gangrene and Other Clostridial Infections / Lawrence C. Madoff 43.Clostridium Difficile Associated Disease, Including Pseudomembranous Colitis / Stuart Johnson pt. 3 Diseases Caused by Gram-Negative Bacteria 44.Meningococcal Infections / Lee M. Wetzler 45.Gonococcal Infections / Peter A. Rice 46.Moraxella Infections / Daniel M. Musher 47.Haemophilus Infections / Timothy F. Murphy 48.Infections Due to the HACEK Group and Miscellaneous Gram-Negative Bacteria / Dennis L. Kasper 49.Legionella Infection / Victor L. Yu 50.Pertussis and Other Bordetella Infections / Scott A. Halperin 51.Diseases Caused by Gram-Negative Enteric Bacilli / James R. Johnson 52.Helicobacter Pylori Infections / Martin J. Blaser 53.Infections Due to Pseudomonas Species and Related Organisms / Reuben Ramphal 54.Salmonellosis / Samuel I. Miller 55.Shigellosis / Jean Bergounioux Note continued: 56.Infections Due to Campylobacter and Related Species / Martin J. Blaser 57.Cholera and Other Vibrioses / Gerald T. Keusch 58.Brucellosis / Nicholas J. Beeching 59.Tularemia / Gordon E. Schutze 60.Plague and Other Yersinia Infections / Grant L. Campbell 61.Bartonella Infections, Including Cat-Scratch Disease / Emily Darby 62.Donovanosis / Gavin Hart pt. 4 Miscellaneous Bacterial Infections 63.Nocardiosis / Gregory A. Filice 64.Actinomycosis / Thomas A. Russo 65.Infections Due to Mixed Anaerobic Organisms / Ronit Cohen-Poradosu pt. 5 Mycobacterial Diseases 66.Tuberculosis / Richard J. O'Brien 67.Leprosy (Hansen's Disease) / Robert H. Gelber 68.Nontuberculous Mycobacteria / C. Fordham von Reyn 69.Antimycobacterial Agents / David E. Griffith pt. 6 Spirochetal Diseases 70.Syphilis / Sheila A. Lukehart 71.Endemic Treponematoses / Sheila A. Lukehart 72.Leptospirosis / Rudy Hartskeerl Note continued: 73.Relapsing Fever / David T. Dennis 74.Lyme Borreliosis / Allen C. Steere pt. 7 Diseases Caused by Rickettsiae, Mycoplasmas, and Chlamydiae 75.Rickettsial Diseases / Thomas Marrie 76.Infections Due to Mycoplasmas / William M. McCormack 77.Chalamydial Infections / Walter E. Stamm SECTION V VIRAL INFECTIONS pt. 1 Viral Diseases: General Considerations 78.Medical Virology / Elliott Kieff 79.Antiviral Chemotherapy, Excluding Antiretroviral Drugs / Raphael Dolin pt. 2 Infections Due to DNA Viruses 80.Herpes Simplex Viruses / Lawrence Corey 81.Varicella-Zoster Virus Infections / Richard J. Whitley 82.Epstein-Barr Virus Infections, Including Infections Mononucleosis / Jeffrey I. Cohen 83.Cytomegalovirus and Human Herpesvirus Types 6, 7, and 8 / Martin S. Hirsch 84.Molluscum Contagiosum, Monkeypox, and Other Poxviruses, Excluding Smallpox Virus / Fred Wang 85.Parvovirus Infections / Kevin E. Brown Note continued: 86.Human Papillomavirus Infections / Richard C. Reichman pt. 3 Infections Due to DNA and RNA Respiratory Viruses 87.Common Viral Respiratory Infections and Severe Acute Respiratory Syndrome (SARS) / Raphael Dolin 88.Influenza / Raphael Dolin pt. 4 Infections Due to Human Immunodeficiency Virus and Other Human Retroviruses 89.The Human Retroviruses / Anthony S. Fauci 90.Human Immunodeficiency Virus Disease: AIDS and Related Disorders / H. Clifford Lane pt. 5 Infections Due to RNA Viruses 91.Viral Gastroenteritis / Roger I. Glass 92.Acute Viral Hepatities / Jules L. Dienstag 93.Chronic Hepatitis / Jules L. Dienstag 94.Enteroviruses and Reoviruses / Jeffrey I. Cohen 95.Measles (Rubeola) / Anne Gershon 96.Rubella (German Measles) / Anne Gershon 97.Mumps / Anne Gershon 98.Rabies and Other Rhabdovirus Infections / Eri C. Johannsen 99.Infections Caused by Arthropod-and Rodent-Borne Viruses / Clarence J. Peters Note continued: 100.Ebola and Marburg Viruses / Clarence J. Peters SECTION VI PRION DISEASES 101.Prion Diseases / Bruce L. Miller SECTION VII FUNGAL AND ALGAL INFECTIONS 102.Diagnosis and Treatment of Fungal Infections / John E. Edwards, Jr 103.Histoplasmosis / L. Joseph Wheat 104.Coccidioidomycosis / Neil M. Ampel 105.Blastomycosis / Donna C. Sullivan 106.Cryptococcosis / Arturo Casadevall 107.Candidiasis / John E. Edwards, Jr 108.Aspergillosis / David W. Denning 109.Mucormycosis / Alan M. Sugar 110.Miscallaneous Mycoses and Algal Infections / Donna C. Sullivan 111.Pneumocystic Infection / Peter D. Walzer SECTION VIII PROTOZOAL AND HELMINTHIC INFECTIONS pt. 1 Parasitic Infections: General Considerations 112.Laboratory Diagnosis of Parasitic Infections / Charles E. Davis 113.Agents Used to Treat Parasitic Infections / Thomas A. Moore 114.Pharamacology of Agents Used to Treat Parasitic Infections / Thomas A. Moore Note continued: pt. 2 Protozoal Infections 115.Amebiasis and Infection With Free-Living Amebas / Sharon L. Reed 116.Malaria / Joel G. Breman 117.Babesiosis / Edouard Vannier 118.Atlas of Blood Smears of Malaria and Babesiosis / Joel G. Breman 119.Leishmaniasis / Barbara L. Herwaldt 120.Trypanosomiasis / Louis V. Kirchhoff 121.Toxoplasma Infections / Lloyd H. Kasper 122.Protozoal Intestinal Infections and Trichomoniasis / Peter F. Weller pt. 3 Helminthic Infections 123.Trichinella and Other Tissue Nematodes / Peter F. Weller 124.Intestinal Nematodes / Thomas B. Nutman 125.Filarial and Related Infections / Peter F. Weller 126.Schistosomiasis and Other Trematode Infections / Adel A.F. Mahamoud 127.Cestodes / Peter F. Weller
Includes bibliographical references and index.
Keywords: COMMUNICABLE DISEASES